Respon Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq) Terhadap Pemberian Dolomit dan Pupuk Fosfor - Purwati Purwati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2013)
The experiment aimed to identify the growing of palm oil seedling (Elaeis guineensis Jacq) upon the aplication of Dolomite and Phosporus fertilizer, as well as its interaction, and to find the proper dosage of dolomite and Phosporus fertilizer for palm oil seedling. The experiment lasted for four months, from Oktober 2010 to Januari 2011, at the screen house agriculture faculty Widya Gama Mahakam university,  Sempaja Samarinda City. The experiment employed Completely Randomized Block Design with Factorial 3 x 4 and three replications. The first factor was Phospor fertilizer (P) : 1,5 g SP-36/polybag (p1); 2,0 g SP-36/polybag (p2); 2,5 g SP-36/polybag (p3). And the second factor was dolomite (D): no dolomite (d0);10 g dolomite/polybag (d1); 15 10 g dolomite/polybag (d2); 20 g dolomite/polybag (d3).Results at the experiment showed that: (1) significant responses of phosphorus  fertilizer on the parameters of number of leaf at the stage of 90 old days and diameter of stem at the stage of 60 old days; (2) significant responses on the application of Dolomit on diameter of stem at the stage of 30 and 60 old days; (3) significant responses the interaction between phosporus  fertilizer and Dolomit application on number of leaf at the stage of 60 old days.